The classification and framing of the curriculum: a case of integrated studies - Chien, Robyn Kay (Curtin University, 2004)
This study focuses on curriculum integration for several reasons. Firstly, because there appeared to be no clear definition of integration nor a consensus on what constituted good integration. Secondly, there were few studies on integration and the type of learning involved. I believe that a study looking at an integrated unit in depth should help to shed light on what integration is and how it can be accommodated within the school system. Thirdly, an opportunity existed to observe such a unit within an established middle school. As integration is purported as being "the way" young adolescents should be taught, a middle school setting seemed ideal to me. I thought that this setting should be far enough removed from the content driven senior school to allow for its complete and uninhibited development, especially given the philosophy of this well developed middle school. Fourthly, I am interested in the potential of integration as a way of focusing on learning outcomes rather than curriculum inputs. My own theoretical perspective, with a heavy leaning toward constructivist ideas, caused me to lean towards qualitative rather than quantitative research methodologies and methods. I wanted to do justice to the study by clearly describing the social context of the school and the curriculum. Basil Bemstein's pedagogic code was seen as a way of providing the framework for the development of such a method of description. As this pedagogic code had seldom been used in a study such as this, a complete investigation of its descriptive and analytic power was seen as being of benefit to future curriculum research. The study involved two major tasks. The first task was to develop the framework to a point that it would provide a descriptive language for the recording and analysis of a school culture.This was done by reconceptualising theories about the sociology of knowledge drawing on research by Bemstein (1971a; 1971b; 1977; 1990; 1996; 2000), Young (1971), Daniels (1987; 1989; 1995; 2001), Morais (1992) and Parker (1994) and modifying the resulting mapping tool developed to suit the complexity of the data gathered. The second task was to apply this framework to the observational data and to derive a description of the culture of the school and the micro-cultures of the two units of study observed within this school. From this description meaning was generated in the form of propositional statements about the development of an integrated unit of study within the culture of a school.